2019
DOI: 10.3389/fphar.2019.00906
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin, a Marine Xanthophyll Isolated From Conticribra weissflogii ND-8: Preventive Anti-Inflammatory Effect in a Mouse Model of Sepsis

Abstract: Background: Fucoxanthin (FX), a xanthophyll pigment which occurs in marine brown algae with remarkable biological properties, has been proven to be safe for consumption by animals. Although FX has various pharmacological effects including anti-inflammatory, anti-tumor, anti-obesity, antioxidant, anti-diabetic, anti-malarial, and anti-lipid, in vivo protective effect against sepsis has not been reported. In this study, we aimed at evaluation the efficacy of the FX in a model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 69 publications
0
57
0
2
Order By: Relevance
“…However, it has been reported that their content might be different depending on environmental factors such as an inhabited area and temperature stress [54]. Furthermore, xanthophyll has been reported to have anti-inflammatory effects on brain inflammation and in LPS-stimulated inflammation [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that their content might be different depending on environmental factors such as an inhabited area and temperature stress [54]. Furthermore, xanthophyll has been reported to have anti-inflammatory effects on brain inflammation and in LPS-stimulated inflammation [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) binds its receptor, CD14, forming immune complexes, which then interact with Toll-like receptors (TLR) to promote intracellular signal transduction and release various inflammatory mediators [ 85 ]. LPS is also an endogenous mediator that induces fever [ 86 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Phycoerythrin is a red protein pigment that is abundant in Rhodophyta and cyanobacteria with antitumor and anti-ageing properties [ 48 ]; it has also been reported as an anti-inflammatory compound [ 49 ]. Fucoxanthin, a xanthophyll-like carotenoid, has also shown many biological properties that include anti-inflammatory effects [ 50 , 51 ].…”
Section: Algae-derived Antiviral Compoundsmentioning
confidence: 99%